Exploring Perceptions of Elementary School Teachers on the Importance of School-Based Life Skills Education. A Case Study - Bushra Mairaj; Najmonnisa Khan (Institute of Business Management, 2021)
There is an unusual increase in the cases of child abuse, early marriages, suicide, physical and mental violence causing a large number of school dropouts in elementary classes. This calls for the requirement to investigate or evaluate the perceptions of teachers about life skills education in public sector elementary schools. The study was conducted using qualitative interviews from twelve teachers of two public schools where life skill education is being taught. Thematic analysis was used for data analysis. The findings of the study revealed that teachers are aware and have a positive attitude towards life skills education. This study will contribute to raising awareness.T